2013
DOI: 10.1007/s10265-013-0560-8
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterisation during seed development of oil palm (Elaeis guineensis)

Abstract: Developmental biochemical information is a vital base for the elucidation of seed physiology and metabolism. However, no data regarding the biochemical profile of oil palm (Elaeis guineensis Jacq.) seed development has been reported thus far. In this study, the biochemical changes in the developing oil palm seed were investigated to study their developmental pattern. The biochemical composition found in the seed differed significantly among the developmental stages. During early seed development, the water, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…The oil palm fruit typically exhibits biphasic growth with an initial growth spurt between ~4 and 9 WAA. Further, significant biochemical changes are observed starting at 8 WAA and up to 10 WAA during the transition phase between a metabolic sink and a storage sink25. Therefore, 8 WAA was chosen to examine expression of anthocyanin biosynthetic genes, avoiding later stages when expression of other mesocarp genes occurs that share the phenylpropanoid pathway, such as those involved in polyphenol biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The oil palm fruit typically exhibits biphasic growth with an initial growth spurt between ~4 and 9 WAA. Further, significant biochemical changes are observed starting at 8 WAA and up to 10 WAA during the transition phase between a metabolic sink and a storage sink25. Therefore, 8 WAA was chosen to examine expression of anthocyanin biosynthetic genes, avoiding later stages when expression of other mesocarp genes occurs that share the phenylpropanoid pathway, such as those involved in polyphenol biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of histochemical observations, it was found that the longer the seed stored, the less the fat content in endosperm cell tissue. Kok et al (2013) stated that the fat content in oil palm seeds reached 55% of the total dry weight of the seeds, followed by carbohydrate content of 18% and protein content of 17%. Bewley et al (2013) stated the composition of fat, carbohydrate, and protein content in oil palm reached 49%, 28%, and 9%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The histology of the deterioration of oil palm seed content has not been much researched, despite it is important. Research on the histochemical observations of oil palm embryos is still limited to the histology of embryo formation from initiation to adult embryos (Kok et al, 2013;Kok et al, 2015). However, publications regarding the histochemistry of oil palm embryos from physiological maturity level, or as food reserves, to the deterioration or degradation process have not been published.…”
Section: Introductionmentioning
confidence: 99%
“…However, extracting high quality total RNA from oil palm fruit is difficult due to the presence of lipids, polysaccharides, protein, polyphenols and other secondary metabolites (Kok et al, 2013). Whole fruit tissues of oil palm comprise of epicarp, mesocarp, endocarp and kernel (endosperm and embryo).…”
Section: Isolation Of High Quality Total Rna From Various Tissues Of mentioning
confidence: 99%